Arabic Language Learning Methods to Improve Maharatul Kalam at the Amal Jama'I Islamic Boarding School in Bojong Cikembar (Communicative Language Teaching Approach) - Nidaul Jannah; Farida Nur Rahma; Meitha Kartika Herdiyanti; Annisa Tsabita; Akiela Zhafiera Fitri (CV Edujavare Publishing, 2026)
This study aims to analyze the application of the Communicative Language Teaching (CLT) method in improving the speaking skills (maharatul kalam) of students at the Amal Jama'i Cikembar Sukabumi Islamic Boarding School. The study used a qualitative approach with a narrative-descriptive method. Data were obtained through observation, interviews, documentation, and triangulation, then analyzed using the Miles and Huberman model. The results showed that the application of CLT was carried out systematically through the planning, implementation, and evaluation stages of learning oriented towards real communication. Learning took place interactively with dialogue, discussion, and role-play techniques, and placed students as active subjects, while the teacher acted as a facilitator and motivator, and used the language of instruction using Arabic. The result was a significant increase in students' speaking skills, vocabulary mastery, and self-confidence. Supporting factors included a conducive language environment and language habituation programs, while obstacles included differences in students' abilities, limited time, and learning media. Overall, CLT proved effective in improving maharatul kalam and the affective aspects of students in learning Arabic.